Estrategias didácticas en el desarrollo de la grafía en segundo de Básica de la Unidad Educativa Fe y Alegría de la ciudad de Riobamba durante el año lectivo 2022- 2023. - Pilco Argos, Liliana Maritza (2023)
The purpose of this research was to analyze the didactic strategies and the development of spelling in the second grade students of the Fe y Alegría Educational Unit of the city of Riobamba during the 2022-2023 school year, with a qualitative approach that aims to describe the elements involved in the identified problem, in this case the weakening of the spelling due to the estimated population, which consisted of 22 teachers and 526 students of the Basic General Education level, from whom a non-probabilistic sample of 35 was taken. students and a second-grade teacher. Participant observation was used as a technique and as an instrument the observation sheet with 16 items for students, with descriptors related to the development of spelling at the evolutionary moment from 6 to 7 years and for teachers an interview that had 10 questions. They were used to collect information and know the level of knowledge and preparation of the teacher for the implementation of didactic strategies during the writing process of the second year of Basic General Education. Among the most relevant research findings is that most of the observed students present omission of letters in the word and errors in morphology.